Structural Visualization of Septum Formation in Staphylococcus warneri Using Atomic Force Microscopy - Su, Hai-Nan (J Bacteriol, 2020)
Cell division of Staphylococcus adopts a “popping” mechanism that mediates extremely rapid separation of the septum. Elucidating the structure of the septum is crucial for understanding this exceptional bacterial cell division mechanism. Here, the septum structure of Staphylococcus warneri was extensively characterized using high-speed time-lapse confocal microscopy, atomic force microscopy, and electron microscopy. The cells of S. warneri divide in a fast popping manner on a millisecond timescale. Our results show that the septum is composed of two separable layers, providing a structural basis for the ultrafast daughter cell separation. The septum is formed progressively toward the center with nonuniform thickness of the septal disk in radial directions. The peptidoglycan on the inner surface of double-layered septa is organized into concentric rings, which are generated along with septum formation. Moreover, this study signifies the importance of new septum formation in initiating new cell cycles. This work unravels the structural basis underlying the popping mechanism that drives S. warneri cell division and reveals a generic structure of the bacterial cell. IMPORTANCE This work shows that the septum of Staphylococcus warneri is composed of two layers and that the peptidoglycan on the inner surface of the double-layered septum is organized into concentric rings. Moreover, new cell cycles of S. warneri can be initiated before the previous cell cycle is complete. This work advances our knowledge about a basic structure of bacterial cell and provides information on the double-layered structure of the septum for bacteria that divide with the “popping” mechanism.